Deadly cure : a novel - Goldstone, Lawrence, 1947- (Pegasus Books, 2017)
"In 1899, in Brooklyn, New York, Dr. Noah Whitestone is called urgently to his wealthy neighbor's house to treat a five-year-old boy with a shocking set of symptoms. When the child dies suddenly later that night, Noah is accused by the boy's regular physician--the powerful and politically connected Dr. Arnold Frias--of prescribing a lethal dose of laudanum. To prove his innocence, Noah must investigate the murder--for it must be murder--and confront the man whom he is convinced is the real killer. His investigation leads him to a reporter for a muckraking magazine and a beautiful radical editor who are convinced that a secret, experimental drug from Germany has caused the death of at least five local children, and possibly many more. By degrees, Noah is drawn into a dangerous world of drugs, criminals, and politics, which threatens not just his career but also his life." --